MANAJEMEN PENINGKATAN MUTU ADMINISTRASI SEKOLAH - Fajar Sumantri Fajar Sumantri (Manajer Pendididikan, 2015)
The purpose of this study was to describe the management of quality improvement of school administration at senior high school number 2 Muara Beliti Musi Rawas Regency. Thisstudy used a qualitative descriptive method. The subject is principal, vice principal, head of the administration, teachers and school treasurer. Data collection was done by observation, interviews, and documentation. Data analysis was performed with a descriptive qualitative through the reduction of data, display data, and data verification. The results showed that improved quality management school has been going according to plan with the condition, and the programs of the school.Keyword: management, quality improvement, school administration